Pengaruh Literasi Keuangan Syariah, Digital Marketing dan Aksesibilitas Terhadap Minat Menabung Generasi Z pada Bank Syariah - Sadiah, Mahmudah; Amalia Puspa, Devi (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2024)
This research aims to determine the influence of sharia financial literacy, digital marketing and accessibility factors on generation Z's interest in saving at sharia banks. This research uses quantitative methods with multiple linear regression analysis and is processed using the SPSS version 25 program. Data was obtained through a questionnaire shown to generation Z in Jepara Regency. This research took 97 respondents as samples which were calculated using the Slovin formula with a purposive sampling technique. The results of the research show that based on the results of hypothesis testing, the results show that sharia financial literacy, digital marketing and accessibility have a significant positive effect on generation Z's interest in saving at sharia banks.